The relationship between Internet addiction and academic burnout in undergraduates: a chain mediation model - Wei, Zhixia; Che Hassan, Norlizah; Hassan, Siti Aishah; Ismail, Normala; Gu, Xiaoxia; Dong, Jingyi (BioMed Central, 2025)
Background: In the hybrid teaching context, the impact of Internet addiction on academic burnout and its underlying mechanism is still unclear. This study aims to investigate the effect of Internet addiction on academic burnout, and the chain mediating effect of academic engagement and academic self-efficacy in the relationship between Internet addiction and academic burnout. Methods: This study adopted a quantitative and correlational research design. A stratified random sampling method was used and a sample of 534 undergraduates (148 male and 386 female) from three normal universities participated in this study. Instruments used were the Chinese version of the Internet Addiction Test, the Chinese version of the Utrecht Work Engagement Scale-Student, the Chinese version of the Academic Self-efficacy Scale, and the Learning Burnout Scale of Undergraduates. Data were collected through self-report questionnaires and structural equation modeling was adopted to test the hypotheses using AMOS 24.0 software. Results: The findings revealed that Internet addiction demonstrated a statistically significant positive association with academic burnout among undergraduate students. Analysis of mediating effects indicated that academic engagement served as a significant mediator in the relationship between Internet addiction and academic burnout. However, academic self-efficacy failed to exhibit a significant mediating effect between these variables. Further examination revealed a significant chain mediating effect of academic engagement and academic self-efficacy in the relationship between Internet addiction and academic burnout. Conclusion: Internet addiction influences academic burnout of undergraduate students both directly and indirectly through academic engagement and academic self-efficacy. Effective interventions could be implemented in universities to mitigate the negative effects of Internet addiction by enhancing academic engagement and academic self-efficacy, which may reduce students’ vulnerability to academic burnout and its associated educational consequences such as course withdrawal, decreased academic performance, or dropping out.